Digitalization without Diversification: Constraints and Potentials of Azerbaijan's ICT Sector in the Post-Oil Economy - Gubad Ibadoghlu (ZBW - Leibniz Information Centre for Economics, 2025)
The Information and Communication Technologies (ICT) sector holds strategic importance for Azerbaijan's ambitions to diversify beyond hydrocarbons and modernize its national economy. Yet, despite extensive public investment and infrastructure development, the sector's contribution to GDP, employment, and exports remains limited. Drawing on official statistics and policy documents for 2020-2025, this study examines the performance, structure, and constraints of Azerbaijan's ICT and digital economy. In 2024, ICT accounted for only 1.8 percent of GDP, 0.036 percent of total exports, and 1.4 percent of national employment. Research and development (R&D) expenditure remained below 0.3 percent of GDP, while Azerbaijan ranked 94th in the 2025 Global Innovation Index-well behind regional peers. The paper attributes the sector's underperformance to low innovation intensity, weak private-sector participation, and overreliance on state-led infrastructure projects such as Azercosmos, which, while symbolically important, have not produced broad technological spillovers. At the same time, Azerbaijan has made measurable progress in digital finance, with non-cash payments rising from 30 percent in 2021 to 64.2 percent in 2024. These advances, however, have not translated into a robust, innovation-driven ICT ecosystem. The findings suggest that Azerbaijan's digital transformation remains infrastructure-heavy but innovation-light, requiring a shift toward policies that promote R&D investment, entrepreneurial capacity, and integration into global digital value chains.
Keywords: 330; Azerbaijan; Digital Economy; ICT Sector; Innovation; R&D; Diversification; Azercosmos; E-Governance; Non-Cash Payments; Digital Transformation